SECONDARY CITY TOURIUM PROMOTION WITH DIGITAL MEDIA TECHNOLOGY - Keitpiriya , Sathaporn; Busaman, Sarawut; Phetcaot, Kamom; Chaiwong , Aunchan (Journal of MCU Nakhondhat, 2020)
Thailand is a top tourist destination for foreign tourists. According to tourism, Thailand has identified the provinces that generate the main income from tourism. Divided into 22 main cities and 55 sub - cities, the secondary city is a unique city. It is an increasing attraction of both Thai and foreign tourists to visit the secondary city. Part of the growth of tourism Driven by the advancement of Internet of Things (IoT) That facilitates tourists Can search for information Book flight tickets, book rooms and pay more conveniently. For entrepreneurs Must create digital media in such a way that the entrepreneurs in the secondary cities come together in the same group of entrepreneurs. Service in the same area Or have specific expertise in the same subject as an online community It needs to create an appeal that is a deciding factor in travel. Description of properties The beauty of the attraction Also need to increase communication in terms of inspiration Will encourage tourists to decide to travel Internet of Things (IoT) must be developed as part of the tourists. To be the medium between the main needs of tourists and the harmony with the attractions As a result, tourists have the confidence to travel. Be impressed Comfort Good environment Sharing of information Sharing various experiences with each other, pictures of travel times with good feelings and beautiful scenery in the past, as well as creating tourism development, beneficial to decision making, have positive feelings on the use of digital media technology. Causing more behavior to use digital media technology for tourism management